Development of knowledge management measurement framework and its application in China ship building industry - LIm, Daw See Francis (2018)
Knowledge Management (KM) in this research refers to a process that dives deep into an organization and analyzes operational metrics to understand and help the enterprise make use of knowledge both explicit and tacit, facilitate a state of knowledge awareness and sustain the knowledge managing and learning process. This novelty of the research is its first attempt to combine China's KM implementation issues statistics, literature review on KM model and KM CSFs, integrating with research objectives findings to develop a KM framework for China SME shipyards. This framework interlinks the knowledge cycle of knowledge acquisition, application and improvement continuously within organization by 3 KM domains of organization entity, people interaction and organization memory, formulated by 12 KM CSFs derived. The uniqueness of this framework is it emphasis on people. Organization entity involves people support of top management to motivate and drive organizational culture to embrace KM. Continuous organization knowledge improvement involve people interaction to facilitate knowledge processes through socialization programs, training and building of trustworthy team. People are the one who contribute to organization memory by retain and update organization knowledge for effective reprocessing and retrieval via information technology. The survey took the form of structured interview in five stages of field study with eight sets of survey questionnaires. AHP method is applied to quantify practices and translate it into measurable absolute numbers. Result showed that one third of China SME shipyards are NOT Ready for KM implementation. Among the deficiencies, knowledge structure is the first limitation, followed by the knowledge content and training. The value of this research is to highlight and illustrate to enterprises the opportunity of the application of KM Framework could continuously improve their organization knowledge from operating processes through systematic knowledge acquisition and application, to gain their competitiveness and sustainability in long term. In short term, this KM framework by application could answer to the question that all China SME shipyards unanimously asked “Do you think my shipyard is Ready to implement Knowledge Management ?”